Hubungan Keterlibatan Ayah dengan Insecure Attachment pada Wanita Dewasa Awal yang Menjalin Hubungan Romantis - Anastasya Syafira Miranda; Untung Subroto (Lembaga Yasin AlSys, 2026)
Father involvement in parenting is a crucial factor shaping the emotional and relational development of daughters into adulthood, yet studies that specifically examine its association with insecure attachment among early adult women in romantic relationships remain limited. This study aimed to investigate the relationship between father involvement and insecure attachment in early adult women who are currently in romantic relationships. A quantitative method with a correlational design was employed, involving 237 female participants aged 18–25 years who had been dating or engaged for a minimum of six months. The instruments used were the Perceived Father Involvement (PFI) scale to measure father involvement and the Experiences in Close Relationships–Revised (ECR–R) to measure attachment insecurity. Data were analyzed using a correlation test, which yielded a coefficient of r = -0.728, indicating a strong negative relationship between father involvement and attachment insecurity. This means that the higher the perceived father involvement, the lower the level of insecure attachment in romantic relationships. These findings underscore the importance of fathers’ emotional presence in fostering more secure attachment patterns in early adult women and open opportunities for developing interventions that incorporate the quality of the father–child relationship as a promotive effort for relational health in adulthood.